Aerial targeting and the laws of war : a socio-legal study of the achievement of compliance - Holder, Alexander P. (Routledge, 2026)
A ground-breaking socio-legal investigation of the in situ legal considerations involved in targeting and the use of force, Aerial Targeting and the Laws of War develops a new kind of evidence base for international action relating to the protection of civilians.Investigating the materials surrounding a civilian casualty incident that took place in Afghanistan in 2010, the book explores how a single strike - which was conducted in light of intelligence gathered by a militarised drone crew and resulted in the deaths of at least 15 civilians - became a lawful strike, that is, a strike that was deemed to have been compliant with the laws of war both at the point at which munitions were released and following two internal investigations. Through an ethnomethodological engagement with the transcripts, interviews, reports, and other materials associated with the incident, Alexander P. Holder examines the methods by which military personnel produce and maintain legitimate targets for the use of force.Re-focusing debates surrounding civilian harm upon the praxeological details of the military practices, which generate such harms, this book will appeal to scholars of sociology, military studies, and socio-legal studies with interests in the rules of war and ethnomethodological approaches to research.
Keywords: Aggression (International law); Operational art (Military science); War -- Protection of civilians.; War (International law); elektronické knihy; electronic books